Dental polymerizable composition

Incorporating gadolinium-containing glass into dental polymerizable compositions addresses the issue of reduced operability from excessive barium glass, achieving high X-ray contrast and maintaining composition flexibility.

JP7608689B2Active Publication Date: 2025-01-07GC R&D CORP JP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021062368
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-01-07
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Dental polymerizable compositions with high X-ray contrast properties tend to become hard and reduce operability when barium glass is added in large amounts.

Method used

Incorporating gadolinium-containing glass into the dental polymerizable composition, which enhances X-ray opacity without the need for excessive barium glass, thereby maintaining operability.

Benefits of technology

The composition achieves high X-ray contrast properties while preserving operability by using gadolinium-containing glass, reducing the necessity for barium glass and preventing hardness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608689000001
    Figure 0007608689000001
  • Figure 0007608689000002
    Figure 0007608689000002
Patent Text Reader

Abstract

To provide a polymerizable dental composition having high radiopaque properties without a decrease in operability.SOLUTION: A polymerizable dental composition contains a (meth)acrylate compound and glass, where the glass contains gadolinium.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dental polymerizable composition. [Background technology]

[0002] As an example of a dental polymerizable composition, there is known a dental polymerizable composition having a first agent containing a (meth)acrylate, a thiourea derivative, and a vanadium compound, and a second agent containing a (meth)acrylate and an organic peroxide (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-51856 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, there is a demand for a dental polymerizable composition having higher X-ray contrast (X-ray opacity). One method for improving X-ray contrast is to include barium glass, but when a large amount of barium glass is added, the composition becomes hard, and the operability is reduced.

[0005] An object of the present invention is to provide a dental polymerizable composition having high X-ray contrast properties without impairing operability. [Means for solving the problem]

[0006] A dental polymerizable composition according to one aspect of the present invention is a dental polymerizable composition containing a (meth)acrylate compound and glass, the glass being gadolinium. and barium Contains: Effect of the Invention

[0007] According to one aspect of the present invention, a dental polymerizable composition having high X-ray contrast properties without reducing operability can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, an embodiment of the present invention will be described in detail.

[0009] The dental polymerizable composition according to the present embodiment contains a (meth)acrylate compound and glass. In this specification, the polymerizable composition refers to a composition that has the function of being polymerized.

[0010] The (meth)acrylate compound contained in the dental polymerizable composition refers to a monomer, oligomer, or prepolymer having one or more (meth)acryloyloxy groups of (meth)acrylate. In this specification, (meth)acrylate refers to one or both of acrylate and methacrylate.

[0011] The (meth)acrylate is not particularly limited, and may be, for example, a (meth)acrylate having an acid group, a (meth)acrylate not having an acid group, or both.

[0012] The (meth)acrylate having an acid group may have a plurality of acid groups.

[0013] Moreover, instead of the (meth)acrylate having an acid group, an acid chloride, an alkali metal salt, or an amine salt of the (meth)acrylate having an acid group may be used.

[0014] Examples of the (meth)acrylate having an acid group include (meth)acrylate having a phosphoric acid group, (meth)acrylate having a pyrophosphoric acid group, (meth)acrylate having a thiophosphoric acid group, (meth)acrylate having a carboxyl group, (meth)acrylate having a sulfonic acid group, and (meth)acrylate having a phosphonic acid group.

[0015] Examples of the (meth)acrylate having a phosphoric acid group include 2-(meth)acryloyloxyethyl dihydrogen phosphate, bis[2-(meth)acryloyloxyethyl]hydrogen phosphate, 2-(meth)acryloyloxyethyl phenyl hydrogen phosphate, 6-(meth)acryloyloxyhexyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl phenyl hydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 1,3-di(meth)acryloylpropane-2-dihydrogen phosphate, 1,3-di(meth)acryloylpropane-2-phenyl hydrogen phosphate, and bis[5-{2-(meth)acryloyloxyethoxycarbonyl}heptyl]hydrogen phosphate. Among these, 10-methacryloyloxydecyl dihydrogen phosphate is preferred from the viewpoint of improving the adhesiveness of the dental polymerizable composition.

[0016] Examples of (meth)acrylates having a pyrophosphate group include bis[2-(meth)acryloyloxyethyl] pyrophosphate, bis[4-(meth)acryloyloxybutyl] pyrophosphate, bis[6-(meth)acryloyloxyhexyl] pyrophosphate, bis[8-(meth)acryloyloxyoctyl] pyrophosphate, and bis[10-(meth)acryloyloxydecyl] pyrophosphate.

[0017] Examples of the (meth)acrylate having a thiophosphate group include 2-(meth)acryloyloxyethyl dihydrogen thiophosphate, 3-(meth)acryloyloxypropyl dihydrogen thiophosphate, 4-(meth)acryloyloxybutyl dihydrogen thiophosphate, 5-(meth)acryloyloxypentyl dihydrogen thiophosphate, 6-(meth)acryloyloxyhexyl dihydrogen thiophosphate, 7-(meth)acryloyloxyheptyl dihydrogen thiophosphate, 8-(meth)acryloyloxyoctyl dihydrogen thiophosphate, 9-(meth)acryloyloxynonyl dihydrogen thiophosphate, 10-(meth)acryloyloxydecyl dihydrogen thiophosphate, and 11-(meth)acryloyloxyundecyl dihydrogen thiophosphate. Examples of suitable acryloyloxyalkyl dihydrogen thiophosphate include 12-(meth)acryloyloxydodecyl dihydrogen thiophosphate, 13-(meth)acryloyloxytridecyl dihydrogen thiophosphate, 14-(meth)acryloyloxytetradecyl dihydrogen thiophosphate, 15-(meth)acryloyloxypentadecyl dihydrogen thiophosphate, 16-(meth)acryloyloxyhexadecyl dihydrogen thiophosphate, 17-(meth)acryloyloxyheptadecyl dihydrogen thiophosphate, 18-(meth)acryloyloxyoctadecyl dihydrogen thiophosphate, 19-(meth)acryloyloxynonadecyl dihydrogen thiophosphate, and 20-(meth)acryloyloxyicosyl dihydrogen thiophosphate.

[0018] Examples of (meth)acrylates having a carboxyl group include 2-methacryloyloxyethyl succinic acid, 4-(meth)acryloyloxyethyl trimellitic acid, 4-(meth)acryloyloxyethyl trimellitic anhydride, 4-(meth)acryloyloxydecyl trimellitic acid, 4-(meth)acryloyloxydecyl trimellitic anhydride, 11-(meth)acryloyloxy-1,1-undecanedicarboxylic acid, 1,4-di(meth)acryloyloxypyromellitic acid, 2-(meth)acryloyloxyethyl maleic acid, 2-(meth)acryloyloxyethyl phthalic acid, and 2-(meth)acryloyloxyethyl hexahydrophthalic acid. Among these, 2-methacryloyloxyethyl succinic acid is preferred in terms of improving the adhesiveness of the dental polymerizable composition.

[0019] Examples of the (meth)acrylate having a sulfonic acid group include 2-(meth)acrylamide-2-methylpropanesulfonic acid, styrenesulfonic acid, and 2-sulfoethyl (meth)acrylate.

[0020] Examples of the (meth)acrylate having a phosphonic acid group include 2-(meth)acryloyloxyethyl phenyl phosphonate, 5-(meth)acryloyloxypentyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonopropionate, 10-(meth)acryloyloxydecyl-3-phosphonopropionate, 6-(meth)acryloyloxyhexyl-3-phosphonoacetate, and 10-(meth)acryloyloxydecyl-3-phosphonoacetate.

[0021] These (meth)acrylates having an acid group may be used alone or in combination of two or more kinds.

[0022] Among these, (meth)acrylates having an acid group are preferably (meth)acrylates having a phosphate group or a carboxyl group in terms of the solubility of the smear layer on the tooth surface of the dental polymerizable composition, the demineralization of tooth tissue, and in particular, the adhesion to enamel.

[0023] The content of the (meth)acrylate having an acid group in the dental polymerizable composition is not particularly limited, and can be, for example, 0.1% by mass or more and 20% by mass or less, preferably 0.1% by mass or more and 15% by mass or less, and more preferably 0.1% by mass or more and 10% by mass or less. When the content of the (meth)acrylate having an acid group in the dental polymerizable composition is 0.1% by mass or more, the adhesiveness of the dental polymerizable composition to tooth structure is further improved, and when it is 20% by mass or less, the hardening property of the dental polymerizable composition is improved.

[0024] Examples of (meth)acrylates having no acid group include methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, hydroxypropyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-methoxyethyl ... (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-methylhexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, benzyl (meth)acrylate, 2-hydroxy-1,3-di(meth)acryloyloxypropane, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, (meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolmethane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, polybutylene glycol di(meth)acrylate, bisphenol A diglycidyl (meth)acrylate, di-2-(meth)acryloyl octanoate hydroxyethyl-2,2,4-trimethylhexamethylene dicarbamate, 1,3,5-tris[1,3-bis{(meth)acryloyloxy}-2-propoxycarbonylaminohexane]-1,3,5-(1H,3H,5H)triazine-2,4,6-trione, 2,2-bis[4-(3-(meth)acryloyloxy-2-hydroxypropyl)phenyl]propane, and N,N'-(2,2,4-trimethylhexamethylene)bis[2-(aminocarboxy)propane-1,3-diol]tetramethacrylate.

[0025] These (meth)acrylates having no acid group may be used alone or in combination of two or more kinds.

[0026] Among these, as the (meth)acrylate having no acid group, di-2-(meth)acryloyloxyethyl-2,2,4-trimethylhexamethylene dicarbamate and 2-hydroxy-1,3-di(meth)acryloyloxypropane are preferred from the viewpoint of improving the mechanical strength of the cured body of the dental polymerizable composition.

[0027] The content of the (meth)acrylate not having an acid group in the dental polymerizable composition can be from 10% by mass to 95% by mass, preferably from 13% by mass to 90% by mass, and more preferably from 15% by mass to 80% by mass.

[0028] When the content of the (meth)acrylate having no acid group in the dental polymerizable composition is 10% by mass or more, the operability of the dental polymerizable composition can be improved. Also, when the content of the (meth)acrylate having no acid group in the dental polymerizable composition is 95% by mass or less, the mechanical strength of the dental polymerizable crude product can be improved.

[0029] The glass contained in the dental polymerizable composition contains gadolinium. Gadolinium is a rare earth element in which the 4f orbital, which can hold up to 14 electrons, is occupied by seven electrons, which is half of the number of electrons that can be occupied, and all the occupied electrons are unpaired electrons. Since gadolinium has the 4f orbital occupied by seven unpaired electrons in this way, it has the largest magnetic moment of any 4f element.

[0030] In this embodiment, the glass contained in the dental polymerizable composition containing a (meth)acrylate compound contains gadolinium, thereby increasing the X-ray opacity (the property of blocking X-rays without transmitting them when X-rays are irradiated). As a result, in this embodiment, the contrast property of the dental polymerizable composition by X-rays (hereinafter referred to as X-ray contrast property) can be increased.

[0031] In addition, by including such a gadolinium-containing glass in the dental polymerizable composition, it is not necessary to separately include barium glass, or even if it does, the content of barium glass can be reduced. As a result, in this embodiment, the dental polymerizable composition can be prevented from hardening, so that even if the X-ray contrast property is increased, the operability can be prevented from decreasing.

[0032] The gadolinium content in the glass is not particularly limited, but for example, the content of gadolinium oxide (Gd2O3) calculated as oxide is from 1 mass% to 50 mass%, preferably from 3 mass% to 40 mass%, and more preferably from 5 mass% to 30 mass%.

[0033] By making the content of Gd2O3 in the glass 1 mass % or more, it is possible to increase the X-ray opacity and improve the X-ray contrast property. Also, by making the content of Gd2O3 in the glass 50 mass % or less, it is possible to suppress coloring of the dental polymerizable composition after hardening, and it is possible to improve the transparency of the dental polymerizable composition.

[0034] The glass contained in the dental polymerizable composition preferably further contains barium. In this embodiment, the glass contained in the dental polymerizable composition contains not only gadolinium but also barium, so that the content of gadolinium can be reduced while maintaining high X-ray contrast.

[0035] In addition, in this embodiment, the glass contained in the dental polymerizable composition contains barium, and the gadolinium content can be reduced, so that in this embodiment, coloring of the dental polymerizable composition after hardening can be suppressed, and the transparency of the dental polymerizable composition can be improved.

[0036] The barium content in the glass is not particularly limited, but for example, the content of barium oxide (BaO) calculated as oxide is from 1 mass% to 50 mass%, preferably from 3 mass% to 40 mass%, and more preferably from 5 mass% to 30 mass%.

[0037] By making the content of BaO in the glass 1% by mass or more, it is possible to increase X-ray opacity and improve X-ray contrast, and by making the content of BaO in the glass 50% by mass or less, it is possible to suppress coloring of the dental polymerizable composition after hardening, and it is possible to improve the transparency of the dental polymerizable composition.

[0038] Furthermore, the total of the gadolinium content and the barium content in the glass is not particularly limited, but for example, the total of the gadolinium oxide (Gd2O3) content and the barium oxide (BaO) content calculated as oxides is 2 mass% or more and 70 mass% or less, preferably 5 mass% or more and 60 mass% or less, and more preferably 10 mass% or more and 50 mass% or less.

[0039] By making the total of the Gd2O3 content and the BaO content in the glass 2 mass% or more, the X-ray opacity can be further improved and the X-ray contrast can be further enhanced. Also, by making the total of the Gd2O3 content and the BaO content in the glass 70 mass% or less, the coloring of the dental polymerizable composition after hardening can be further suppressed and the transparency of the dental polymerizable composition can be further improved.

[0040] The glass contained in the dental polymerizable composition may contain, as other glass components, alkali metals, aluminum, boron, silicon, and fluorine.

[0041] The alkali metal includes lithium, sodium, potassium, etc. These may be contained alone or in combination of two or more.

[0042] The content of alkali metals in the glass is not particularly limited, but for example, the total content of lithium oxide (LiO) and / or sodium oxide (NaO) and / or potassium oxide (KO) calculated as oxide is from 0.001% by mass to 10% by mass, preferably from 0.01% by mass to 5% by mass, and more preferably from 0.1% by mass to 1% by mass.

[0043] By regulating the total content of alkali metals in the glass to between 0.001% by mass and 10% by mass, it is possible to prevent a decrease in the chemical durability and water resistance of the glass.

[0044] The aluminum content in the glass is not particularly limited, but for example, the content of aluminum oxide (Al2O3) calculated as oxide is from 0.1% by mass to 30% by mass, preferably from 0.3% by mass to 25% by mass, and more preferably from 0.5% by mass to 20% by mass.

[0045] By making the content of Al2O3 in the glass 0.1 mass% or more, the chemical durability and mechanical strength of the glass can be improved, and the stability of the glass in the dental polymerizable composition can be increased. In addition, by making the content of Al2O3 in the glass 30 mass% or less, the tendency of the glass to devitrify and the decrease in acid resistance can be prevented.

[0046] The boron content in the glass is not particularly limited, but for example, the content of boron oxide (B2O3) calculated as oxide is 1 mass% or more and 30 mass% or less, preferably 5 mass% or more and 20 mass% or less, and more preferably 10 mass% or more and 15 mass% or less.

[0047] By making the content of B2O3 in the glass 1 mass % or more, the crystallization stability of the glass can be improved, and by making the content of B2O3 in the glass 30 mass % or less, the deterioration of the chemical durability of the glass and the non-uniformity of the refractive index can be prevented.

[0048] The content of silicon (Si) in the glass is not particularly limited. For example, the content of silicon oxide (SiO2) calculated as an oxide is preferably 1 mass % or more and 65 mass % or less, more preferably 1 mass % or more and 60 mass % or less, and even more preferably 1 mass % or more and 55 mass % or less.

[0049] By making the SiO2 content in the glass 1 mass% or more, it is possible to adjust the viscosity of the dental polymerizable composition containing the glass, and to increase the mechanical strength of the dental polymerizable composition. In addition, by making the SiO2 content in the glass 65 mass% or less, it is possible to prevent the deterioration of the X-ray opacity of the dental polymerizable composition containing the glass.

[0050] The content of fluorine (F) in the glass is not particularly limited. The content of fluorine in the glass is 0.1 mass% or more and 30 mass% or less, preferably 0.3 mass% or more and 20 mass% or less, and more preferably 0.5 mass% or more and 10 mass% or less.

[0051] By adjusting the F content in the glass to 30 mass % or less, it becomes easy to adjust the viscosity of a dental polymerizable composition containing the glass.

[0052] The amount of glass in the dental polymerizable composition is, for example, preferably from 40% by mass to 90% by mass, more preferably from 50% by mass to 80% by mass, and even more preferably from 60% by mass to 70% by mass.

[0053] When the content of glass in the dental polymerizable composition is 40% by mass or more, the dental polymerizable composition containing the glass can be given high X-ray contrast and can have improved mechanical strength. When the content of glass in the dental polymerizable composition is 90% by mass or less, the viscosity of the dental polymerizable composition containing the glass can be reduced, and the handling property of the dental polymerizable composition can be improved.

[0054] In the dental polymerizable composition of the present embodiment, the refractive index nd of the glass contained in the dental polymerizable composition is 1.4 to 1.7, preferably 1.45 to 1.65, more preferably 1.5 to 1.6. In this specification, the refractive index nd means the refractive index at the D line (light having a wavelength of 589 nm).

[0055] When the refractive index nd of the glass contained in the dental polymerizable composition is 1.4 or more and 1.6 or less, the difference with the refractive index of the matrix component in the dental polymerizable composition becomes small, and the transparency of the obtained cured body of the dental polymerizable composition becomes high.

[0056] The glass is preferably in the form of a powder (or powder). When the glass is in the form of a powder, the glass can be easily blended into the dental polymerizable composition.

[0057] The glass particle size is preferably 0.01 μm or more and 20 μm or less, more preferably 0.05 μm or more and 10 μm or less, and further preferably 0.1 μm or more and 1 μm or less, in terms of median diameter. Here, the particle size means the average particle size defined by the median diameter.

[0058] When the glass powder is used as a glass powder for a dental polymerizable composition, the handling property of the dental polymerizable composition is improved when the glass powder has a particle size of 0.01 μm or more, and when the glass powder has a particle size of 20 μm or less, the wear resistance of the hardened product of the dental polymerizable composition is improved.

[0059] The dental polymerizable composition of the present embodiment preferably contains an inorganic filler. Here, the inorganic filler is a filler composed of inorganic components other than gadolinium.

[0060] The inorganic filler component is not particularly limited, but examples thereof include colloidal silica, fine particle silica having a hydrophobic surface, aluminum oxide (excluding aluminum oxide in glass), fluoroaluminosilicate glass, barium glass, etc. These inorganic fillers may be used alone or in combination of two or more.

[0061] The amount of inorganic filler in the dental polymerizable composition is, for example, preferably from 0.01% by mass to 30% by mass, more preferably from 0.05% by mass to 20% by mass, and even more preferably from 0.1% by mass to 10% by mass.

[0062] When the content of the inorganic filler in the dental polymerizable composition is 0.01% by mass or more, the viscosity of the dental polymerizable composition containing the glass is increased, and the operability of the dental polymerizable composition can be improved. When the content of the inorganic filler in the dental polymerizable composition is 30% by mass or less, the viscosity of the dental polymerizable composition containing the glass is not too high, and the high operability of the dental polymerizable composition can be maintained.

[0063] The dental polymerizable composition of the present embodiment may contain other components as long as the other components do not impair the object of the present invention. Examples of other components contained in the dental polymerizable composition include a chemical polymerization initiator, a photopolymerization initiator, and a polymerization inhibitor.

[0064] The chemical polymerization initiator is not particularly limited, and for example, a thiourea derivative, a vanadium compound, a tertiary amine, or an organic peroxide can be used.

[0065] Among chemical polymerization initiators, the thiourea derivatives function as reducing agents.

[0066] The thiourea derivative is not particularly limited, and examples thereof include ethylenethiourea, N-methylthiourea, N-ethylthiourea, N-propylthiourea, N-butylthiourea, N-laurylthiourea, N-phenylthiourea, N-cyclohexylthiourea, N,N-dimethylthiourea, N,N-diethylthiourea, N,N-dipropylthiourea, N,N-dibutylthiourea, N,N-dilaurylthiourea, N,N-diphenylthiourea, N,N-dicyclohexylthiourea, trimethylthiourea, tetramethylthiourea, N-acetylthiourea, N-benzoylthiourea, 1-allyl-3-(2-hydroxyethyl)-2-thiourea, 1-(2-tetrahydrofurfuryl)-2-thiourea, N-tert-butyl-N'-isopropylthiourea, and 2-pyridylthiourea.

[0067] These thiourea derivatives may be used alone or in combination of two or more. Among these, N-benzoylthiourea is preferred from the viewpoint of improving the curability of the dental polymerizable composition.

[0068] The content of the thiourea derivative in the dental polymerizable composition is not particularly limited, but is preferably 0.1% by mass or more and 5% by mass or less, more preferably 0.1% by mass or more and 3% by mass or less, and even more preferably 0.1% by mass or more and 1% by mass or less. When the content of the thiourea derivative in the dental polymerizable composition is 0.1% by mass or more, the hardening property of the dental polymerizable composition is further improved, and when it is 5% by mass or less, the solubility of the thiourea derivative in (meth)acrylate in the dental polymerizable composition is improved.

[0069] The vanadium compound functions as a reducing agent among chemical polymerization initiators.

[0070] The vanadium compound is not particularly limited, and examples thereof include oxovanadium oxalate, vanadyl acetylacetonate, vanadium acetylacetonate, vanadyl stearate, vanadium naphthenate, vanadium benzoylacetonate, etc., and two or more of these may be used in combination. Among these, vanadyl acetylacetonate is preferred from the viewpoint of the hardening property of the dental polymerizable composition.

[0071] The content of the vanadium compound in the dental polymerizable composition is not particularly limited, but is preferably 0.001% by mass or more and 5% by mass or less, more preferably 0.0015% by mass or more and 1% by mass or less, and even more preferably 0.002% by mass or more and 0.1% by mass or less. When the content of the vanadium compound in the dental polymerizable composition is 0.001% by mass or more, the hardening property of the dental polymerizable composition is further improved, and when it is 5% by mass or less, the storage stability of the dental polymerizable composition is further improved.

[0072] Tertiary amines function as reducing agents among chemical polymerization initiators.

[0073] The tertiary amine is not particularly limited, and examples thereof include tertiary aliphatic amines and tertiary aromatic amines.

[0074] Examples of tertiary aliphatic amines include N,N-dimethylaminoethyl methacrylate and triethanolamine.

[0075] Examples of tertiary aromatic amines include alkyl p-dialkylaminobenzoates, 7-dimethylamino-4-methylcoumarin, N,N-dimethylaniline, N,N-dibenzylaniline, N,N-dimethyl-p-toluidine, N,N-diethyl-p-toluidine, N,N-bis(2-hydroxyethyl)-p-toluidine, N,N,2,4,6-pentamethylaniline, N,N,2,4-tetramethylaniline, and N,N-diethyl-2,4,6-trimethylaniline.

[0076] Of these, the tertiary amine is preferably a tertiary aromatic amine, and more preferably an alkyl p-dialkylaminobenzoate.

[0077] Examples of the alkyl p-dialkylaminobenzoate include methyl p-dimethylaminobenzoate, ethyl p-dimethylaminobenzoate, propyl p-dimethylaminobenzoate, amyl p-dimethylaminobenzoate, isoamyl p-dimethylaminobenzoate, ethyl p-diethylaminobenzoate, and propyl p-diethylaminobenzoate.

[0078] These tertiary amines may be used alone or in combination of two or more kinds.

[0079] Among the chemical polymerization initiators, the organic peroxide functions as an oxidizing agent.

[0080] Examples of organic peroxides include benzoyl peroxide, cumene hydroperoxide, t-butyl hydroperoxide, t-amyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, 2,5-dimethyl-2,5-di(hydroperoxy)hexane, p-diisopropylbenzene monohydroperoxide, p-methane hydroperoxide, and pinane hydroperoxide.

[0081] These organic peroxides may be used alone or in combination of two or more. Among these, cumene hydroperoxide is preferred from the viewpoint of the hardening property of the dental polymerizable composition.

[0082] The content of the organic peroxide in the dental polymerizable composition is not particularly limited, but is preferably 0.01% by mass or more and 10% by mass or less, more preferably 0.05% by mass or more and 5% by mass or less, and even more preferably 0.1% by mass or more and 3% by mass or less. When the content of the organic peroxide in the dental polymerizable composition is 0.01% by mass or more, the hardening property of the dental polymerizable composition is further improved, and when it is 10% by mass or less, the operation margin time of the dental polymerizable composition is extended.

[0083] The photopolymerization initiator is not particularly limited, and examples thereof include camphorquinone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, benzil ketal, diacetyl ketal, benzil dimethyl ketal, benzil diethyl ketal, benzil bis(2-methoxyethyl)ketal, 4,4'-dimethyl(benzyl dimethyl ketal), anthraquinone, 1-chloroanthraquinone, 2-chloroanthraquinone, 1,2-benzanthraquinone, 1-hydroxyanthraquinone, 1-methylanthraquinone, 2-ethylanthraquinone, 1-bromo ... Examples of such compounds include trifluoromethylthioxanthone, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, benzophenone, bis(4-dimethylaminophenyl)ketone, and 4,4'-bis(diethylamino)benzophenone.

[0084] These photopolymerization initiators may be used alone or in combination of two or more. Among these, camphorquinone and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide are preferred from the viewpoint of improving the curability of the dental polymerizable composition.

[0085] The content of the photopolymerization initiator in the dental polymerizable composition is not particularly limited, but is preferably 0.001% by mass or more and 1% by mass or less, more preferably 0.005% by mass or more and 0.5% by mass or less, and even more preferably 0.01% by mass or more and 0.3% by mass or less. When the content of the photopolymerization initiator in the dental polymerizable composition is 0.001% by mass or more, the hardening property of the dental polymerizable composition is further improved, and when it is 0.3% by mass or less, the storage stability of the dental polymerizable composition is further improved.

[0086] Examples of the polymerization inhibitor include dibutylhydroxytoluene (2,6-di-tert-butyl-p-cresol) and 6-tert-butyl-2,4-xylenol.

[0087] These polymerization inhibitors may be used alone or in combination of two or more. Among these, dibutylhydroxytoluene is preferred from the viewpoint of improving the curability of the dental polymerizable composition.

[0088] The content of the polymerization inhibitor in the dental polymerizable composition is not particularly limited, but is preferably 0.001% by mass or more and 5% by mass or less, more preferably 0.005% by mass or more and 1% by mass or less, and even more preferably 0.01% by mass or more and 0.1% by mass or less. When the content of the photopolymerization initiator in the dental polymerizable composition is 0.001% by mass or more and 5% by mass or less, the storage stability of the dental polymerizable composition is improved.

[0089] The dental polymerizable composition of the present embodiment has an X-ray contrast property after polymerization and hardening of 200% or more, preferably 250% or more, and more preferably more than 300%, relative to aluminum. In this specification, the X-ray contrast property refers to the X-ray contrast property measured by a test method for X-ray contrast property of dental materials in accordance with ISO 13116.

[0090] In this embodiment, the X-ray contrast property after polymerization and curing is 200% or more relative to aluminum, so that a dental polymerizable composition having high X-ray contrast property can be provided.

[0091] The formulation of the dental polymerizable composition is not particularly limited, and may be, for example, either a two-part type including a first part and a second part, or a one-part type including only a first part.

[0092] In this embodiment, when the dental polymerizable composition is a two-part formulation, the above-mentioned (meth)acrylate compound and the above-mentioned gadolinium-containing glass can be used for both the first and second parts.

[0093] The glass contained in the first and second parts of the two-part type may both contain the barium described above. Also, the glass contained in the first and second parts may both contain the inorganic filler described above.

[0094] The (meth)acrylate compounds contained in the first and second agents of the two-component type may be the above-mentioned (meth)acrylates having no acid group. The (meth)acrylate compound contained in the second agent of the two-component type may further contain the above-mentioned (meth)acrylate having an acid group.

[0095] The first agent of the two-component type may contain the above-mentioned tertiary amine, the above-mentioned photopolymerization initiator, and the above-mentioned polymerization inhibitor as a chemical polymerization initiator, while the one-component type may contain an organic peroxide as a chemical polymerization initiator.

[0096] The first and second agents of the two-agent type may be in the form of a paste, for example.

[0097] The mass ratio of the first agent to the second agent in the dental polymerizable composition of this embodiment is usually 10:1 to 1:10, and preferably 1:5 to 5:1.

[0098] In the dental polymerizable composition of this embodiment, when it is of the two-component type, the first and second components can be kneaded together before use.

[0099] In this embodiment, as described above, even when the dental polymerizable composition is a two-component type containing a first agent and a second agent, the glass contained in the dental polymerizable composition containing a (meth)acrylate compound contains gadolinium, thereby increasing the X-ray opacity. As a result, in this embodiment, even when the dental polymerizable composition is a two-component type, the X-ray contrast property can be increased.

[0100] In addition, by including such a gadolinium-containing glass in the dental polymerizable composition, it is not necessary to separately include barium glass, or even if it does, the content of barium glass can be reduced. As a result, in this embodiment, even if the dental polymerizable composition is a two-component type including a first agent and a second agent, the dental polymerizable composition can be prevented from hardening, so that a decrease in operability can be prevented even if the X-ray contrast property is improved.

[0101] In this embodiment, when the dental polymerizable composition is a one-part type consisting of only a first part, the above-mentioned (meth)acrylate compound and the above-mentioned gadolinium-containing glass can be used.

[0102] The glass contained in the one-component type may contain the above-mentioned barium. Also, the glass contained in the one-component type may contain the above-mentioned inorganic filler.

[0103] The (meth)acrylate compound contained in the one-component type may be the above-mentioned (meth)acrylate having no acid group.

[0104] The one-component type may contain the above-mentioned thiourea derivative as a chemical polymerization initiator, a vanadium compound, a tertiary amine, the above-mentioned photopolymerization initiator, and the above-mentioned polymerization inhibitor.

[0105] The properties of the one-dose formulation include, for example, a paste form.

[0106] In this embodiment, as described above, even when the dental polymerizable composition is a one-component type, the glass contained in the dental polymerizable composition containing a (meth)acrylate compound contains gadolinium, so that the X-ray opacity is increased. As a result, in this embodiment, even when the dental polymerizable composition is a one-component type, the X-ray contrast property can be increased.

[0107] The application of the dental polymerizable composition of the present embodiment is not particularly limited, and it can be used, for example, in various dental materials. Here, examples of dental materials include dental cement, dental adhesive, dental temporary sealing material, dental primer, dental coating material, dental composite resin, dental hard resin, dental cutting resin material, dental temporary restorative material, dental filler, dentifrice, etc. Among these, it is preferably used in dental cement. EXAMPLES

[0108] The present invention will be further described below with reference to examples. In the following, numerical values ​​without units or "%" are based on mass (% by mass) unless otherwise specified.

[0109] <Glass preparation> Glasses (Glasses 1 to 3) having the compositions shown in Table 1 were prepared. Glasses 1 to 3 were obtained by pulverizing each glass into glass powder having a median diameter (average particle size) of 0.4 μm. The refractive indexes of the obtained glass powders (Glasses 1 to 3) were measured. The average particle size and refractive index of Glasses 1 to 3 are shown in Table 1.

[0110] [Table 1]

[0111] [Examples 1 to 7, Comparative Examples 1 to 3] (Preparation of Paste 1) Methacrylate having no acid group, a vanadium compound, a thiourea derivative, a filler, a tertiary amine, a photopolymerization initiator, and a polymerization inhibitor were mixed in the formulation (mass %) shown in Table 2 to obtain paste 1. The fillers mixed in paste 1 include glasses 1 to 3 and inorganic fillers other than glass.

[0112] (Preparation of Paste 2) Methacrylate without an acid group, methacrylate with an acid group, organic peroxide, a filler, and a polymerization inhibitor were mixed in the formulation (mass %) shown in Table 1 to obtain paste 2. The fillers blended in paste 2 include glasses 1 to 3 and inorganic fillers other than glass.

[0113] [Table 2]

[0114] The meanings of the abbreviations in Table 2 are as follows: Bis-GMA 2,2-Bis[4-(3-methacryloyloxy-2-hydroxypropyl)phenyl]propane UDMA: Di-2-methacryloyloxyethyl-2,2,4-trimethylhexamethylene dicarbamate EBDMA: Ethylene glycol dimethacrylate GDMA: 2-hydroxy-1,3-dimethacryloyloxypropane VAA: Vanadyl acetylacetonate NBTU: N-benzoylthiourea Barium glass: Barium glass particles with a median diameter (average particle size) of 0.4 μm (manufactured by Schott, G018-053) Fluoroaluminosilicate glass: Fluoroaluminosilicate glass powder with a median diameter (average particle size) of 2.2 μm Fumed silica powder 1: Aerosil (registered trademark) RX300 (hydrophobic fumed silica) (manufactured by Nippon Aerosil) Fumed silica powder 2: Aerosil (registered trademark) R812 (hydrophobic fumed silica) (manufactured by Nippon Aerosil) Fumed silica powder 2: Aerosil (registered trademark) R972 (hydrophobic fumed silica) (manufactured by Nippon Aerosil) EPA: Ethyl p-dimethylaminobenzoate CQ: Camphorquinone TPO: Phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide BHT: Dibutyl hydroxytoluene HOMS: 2-methacryloyloxyethyl succinate MDP: 10-methacryloyloxydecyl dihydrogen phosphate CHP: Cumene hydroperoxide

[0115] <Fluoroaluminosilicate glass powder> 22g of aluminum oxide, 23g of anhydrous silicic acid, 12g of calcium fluoride, 15g of calcium phosphate, and 28g of strontium fluoride were thoroughly mixed and stirred in a mortar to obtain a batch, which was placed in a ceramic crucible and heated to 1200°C at a heating rate of about 7°C / min in an electric furnace and held for 3 hours. The molten liquid was then poured into water to obtain a quenched glass, which was then pulverized to obtain a fluoroaluminosilicate glass powder. The median diameter (average particle size) of this inorganic powder was 2.2μm.

[0116] Next, in Examples 1 to 6 and Comparative Examples 1 and 2, Pastes 1 and 2 were mixed, and in Example 7 and Comparative Example 3, only Paste 1 was mixed, and operability was evaluated.

[0117] <Ease of use> A mixing tip (MIXPAC, Helical S type, ML2.5-08-S, inner diameter 2.5 mm, length 39.7 mm, volume 0.19 mL) was attached to a syringe (MIXPAC, 5 mL system cartridge SDL X05-01-78) filled with paste 1, 2 or only paste 1. The ratio (volume ratio) of the first agent to the second agent was 1:1 in Examples 1 to 4 and Comparative Example 1, and 3:2 in Examples 5 to 6 and Comparative Example 2. The syringe was set in a jig and compressed and measured with an autograph. The crosshead speed was 10 mm / min, and the maximum point test force was the extrusion hardness (kgf). The evaluation criteria for operability are as follows. The results of the measurement and evaluation are shown in Table 2. Excellent: Extrusion hardness is less than 5.5kgf Unacceptable: Extrusion hardness is 5.5kgf or more

[0118] Next, the X-ray contrast of the cured bodies obtained by polymerizing and curing the pastes 1 and 2 mixed in Examples 1 to 6 and Comparative Examples 1 and 2, and the cured body obtained by polymerizing and curing only the paste 1 mixed in Example 7 and Comparative Example 3 was evaluated.

[0119] <X-ray contrast> The paste was filled into a circular jig (diameter 15 mm, thickness 1 mm) and cured with a light irradiator. The obtained cured body was X-rayed by the X-ray contrast test method for dental materials conforming to ISO 13116, and the % against aluminum was calculated to evaluate the X-ray contrast. The evaluation criteria for the X-ray contrast are as follows. The results of the measurement and evaluation are shown in Table 2. Excellent: % against aluminum exceeds 300% Good: % against aluminum is 200% or more and 300% or less Poor: % against aluminum is less than 200%

[0120] From Table 2, the dental polymerizable composition containing the (meth)acrylate compound and the glass containing gadolinium had good workability and X-ray contrast (Examples 1 to 7).

[0121] On the other hand, the dental polymerizable composition not containing the glass containing gadolinium had poor workability and / or X-ray contrast (Comparative Examples 1 to 3).

[0122] As described above, the embodiments of the present invention have been described. However, the present invention is not limited to specific embodiments, and various modifications and changes are possible within the scope of the invention described in the claims.

Claims

1. A dental polymerizable composition comprising a (meth)acrylate compound and glass, The glass contains gadolinium and barium. Dental polymerizable compositions.

2. Contains inorganic filler, The dental polymerizable composition of claim 1 .

3. The refractive index nd of the glass is 1.4 or more and 1.7 or less. The dental polymerizable composition according to claim 1 or 2.

4. X-ray contrast property after polymerization and hardening is 200% or more compared to aluminum. The dental polymerizable composition according to claim 1 .

5. It is a two-dose type containing a first agent and a second agent. The dental polymerizable composition according to claim 1 .

6. It is a single-dose formulation. The dental polymerizable composition according to claim 1 .

Citation Information

Patent Citations

  • One-step type adhesive composition for dental use

    JP2005247820A

  • Dental composition containing calcium and phosphorus releasing glass

    JP2008520565A

  • Polymerizable composition

    JP2012051856A

  • JPP3497508B

  • Composite resin cement for dental use, primer for dental use and adhesive kit for dental use containing the same

    WO2007088628A1